Medium Effect Size: Korelasi Internalisasi Bentuk Tubuh Ideal dari Media dan Drive for Thinness - Sugiarto, Amanda Anyza; Yudiarso, Ananta (Mahesa Research Center, 2022)
The purpose of this article is to analyze the impact of internalizing ideal body portrayed by media to drive for thinness. Previous researches directly estimate effect size of mass media exposure to body dissatisfaction with the result of small effect size. This meta-analysis considers cognitive dimension in body image evaluation which individuals do, and thus taking ideal body internalization after mass media exposure as one of the variables and analyze the effect size of this variable to drive for thinness. The articles used in this research are taken from ScienceDirect, Psychnet, Springer, Willey Library, Frontiers in Psychology, and Sage Journals database. Several inclusion and exclusion criteria were applied, resulting in 16 articles to be analyzed further. From 16 studies with the total of 5,042 participants, it was found that internalization of ideal body shape affected by mass media contributes medium effect size (r = 0.5) to drive for thinness, which means internalization of ideal body image from mass media only affect drive for thinness moderately. The data used heterogene with no publication bias. It can be concluded that internalization of ideal body image from media is not the only factor which causes drive for thinness. Gender, cultural background, age, and internal factors like self-concept and conformity also contribute to the development of drive for thinness within individuals.